1988
DOI: 10.1063/1.100098
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution focused ion beam lithography

Abstract: Articles you may be interested inHigh-resolution three-dimensional reconstruction: A combined scanning electron microscope and focused ionbeam approach Very high-resolution focused ion beam nanolithography improvement: A new three-dimensional patterning capability J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 9 publications
0
27
0
1
Order By: Relevance
“…It was found that these noria derivatives have high photoreactivity and produce clear line and space patterns with resolutions of 50-70 nm using an EB exposure tool and 26 nm using an EUV exposure tool [15][16][17][18][19][20][21][22][23]. Moreover, we clarified that the sensitivity of the resist materials was consistent with the structure of the cyclic oligomers such as noria, calixarene dimer, cyclodextrin, and pillar [5]arene [24].…”
Section: Introductionmentioning
confidence: 50%
See 1 more Smart Citation
“…It was found that these noria derivatives have high photoreactivity and produce clear line and space patterns with resolutions of 50-70 nm using an EB exposure tool and 26 nm using an EUV exposure tool [15][16][17][18][19][20][21][22][23]. Moreover, we clarified that the sensitivity of the resist materials was consistent with the structure of the cyclic oligomers such as noria, calixarene dimer, cyclodextrin, and pillar [5]arene [24].…”
Section: Introductionmentioning
confidence: 50%
“…Nanolithography technologies have been widely used below the 100 nm node scale, including the 193 nm immersion, electron beam (EB) [1,2], extreme ultraviolet (EUV, 13.5 nm), nanoimprint methods [3,4], and focused ion beam (FIB) lithography [5]. Among these technologies, EUV lithography is one of the most promising nanolithographic technologies for advanced devices to achieve less than 16 nm nodes [6][7][8] and is a potential future lithographic technology for high-volume manufacturing in the microelectronics industry.…”
Section: Introductionmentioning
confidence: 99%
“…Because FIB patterning saves process steps and time, it can be exploited to develop prototypes of both electrical and optical devices [7]- [11]. Direct milling on the surface [12]- [16], sputtering on a polymer layer [17]- [21], and deposition of metal using a high-energy Ga-FIB [22] can generate nanoscale patterns. Furthermore, locally modifying the GaAs surface using FIB bombardment can be applied to the selective growth of InGaAs/InP on GaAs substrate by hydride vapor phase epitaxy technique [23], [24].…”
mentioning
confidence: 99%
“…The regions where the silicon-containing resist layer remains are oxidised during the dry development, thus forming a silicon dioxide mask which protects the lower resist layer and results in positive image formation. Such FIB bilayer resist schemes are capable of achieving nanometer resolution while maintaining high aspect pattern ratio [6,7]. The only one drawback is the use of wet development step, which often results.…”
Section: B Resistpatterning With Wet Developmentmentioning
confidence: 99%
“…It was reported that the dose needed to expose most resists by ions is about two orders of magnitude lower than for electrons [ I ] . The As a solution to this problem, the bilayer resist schemes for FIB lithography have been developed [5,6,7]. These schemes generally utilise a thin silicon-containing resist layer over a thick planarising layer.…”
Section: B Resistpatterning With Wet Developmentmentioning
confidence: 99%